2019
DOI: 10.1055/s-0039-1677795
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacomechanical Catheter-Directed Thrombolysis in Acute Femoral–Popliteal Deep Vein Thrombosis: Analysis from a Stratified Randomized Trial

Abstract: Word countAbstract : 246 Main text: 2836 4 Abstract Background and Objectives: The ATTRACT trial reported that pharmacomechanical catheterdirected thrombolysis (PCDT) did not reduce postthrombotic syndrome (PTS), but reduced moderate-to-severe PTS and the severity of PTS symptoms. In this analysis, we examine the effect of PCDT in patients with femoral-popliteal DVT (without involvement of more proximal veins). Patients/Methods: Within the ATTRACT trial, 300 patients had deep vein thrombosis (DVT) involving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…233 However, no benefit was observed in patients with femoropopliteal DVT. 234 There are several limitations identified with the ATTRACT and CAVA trials. Given the lack of statistical power for the stratified analyses, the ATTRACT investigators recommended that these findings should be confirmed in future research.…”
Section: Summary Of Randomised Trials Evaluating Early Thrombus Removmentioning
confidence: 99%
“…233 However, no benefit was observed in patients with femoropopliteal DVT. 234 There are several limitations identified with the ATTRACT and CAVA trials. Given the lack of statistical power for the stratified analyses, the ATTRACT investigators recommended that these findings should be confirmed in future research.…”
Section: Summary Of Randomised Trials Evaluating Early Thrombus Removmentioning
confidence: 99%
“…A recently published sub-analysis of the ATTRACT trial looked at the femoro-popliteal cases specifically and demonstrated that, for this subgroup of patients, performing pharmaco-mechanical catheter-directed thrombolysis is of no benefit and is associated with an increased bleeding risk (P = 0.032). 250 Sub-analysis on the ilio-femoral cases of the ATTRACT trial, showed that pharmaco-mechanical catheter-directed thrombolysis did not influence the overall occurrence of PTS or recurrent venous thromboembolism. However, it significantly reduced early symptoms (P < 0.01) and, over 24 months, it reduced PTS severity scores (P < 0.01) and resulted in greater improvement in venous disease-specific quality of life (P = 0.029).…”
Section: Acute and Chronic Deep Venous Diseasementioning
confidence: 99%
“…In a prospective nationwide cohort study, they suggested that anticoagulant therapy should be restricted to patients having disseminated intravascular coagulation and high disease severity simultaneously. Also stressing the importance to accurately define target groups, the study from Kearon et al 17 presented an analysis of a sub-group of patients with femoral-popliteal deep vein thrombosis from the recent ATTRACT randomised trial. Although pharmacomechanical interventions combined with thrombolytic therapy, can rapidly remove thrombus and improve outcomes in patients with acute deep vein thrombosis, these benefits could not be observed among the sub-group for whom this was even associated with increased bleeding.…”
Section: Defining Narrower Target Groups To Fine-tune Clinical Managementioning
confidence: 99%